Evaluation of Administrative Service Quality Towards JKN Patient Satisfaction (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2018)
Based on BPJS Kesehatan data, there was a decrease in Participant Satisfaction Index by 0.3% in 2016. The number of outpatient visits in RSUD KRT. Setjonegoro Wonosobo has decreased in 2016. Based on preliminary study, there were problems mainly related to health services provided by RSUD KRT. Setjonegoro Wonosobo. The purpose of this study was to determine how the quality of administrative services affect the satisfaction of JKN patients. This research used qualitative research methods. Data collection was conducted using observation and interview techniques. The results showed that the quality of administrative services in RSUD KRT. Setjonegoro seen from the dimensions of tangibles, reliability, responsiveness, assurance, and empathy is good. All the main informants were satisfied enough with the health services provided by the hospital. The advice given was to improve the performance in by conducting regular evaluation of the services provided.